The Matter of Mind : Reason and Experience in the Age of Descartes - Braider, Christopher, 1950- (Book collections on Project MUSE., 2012)
The Matter of Mind presents studies drawn from a range of disciplines and examines the paintings of Nicolas Poussin, the drama of Pierre Corneille, and the theology of Blaise Pascal. Braider argues that if early modern thought converged on a single model, then it was the experimental picture based on everyday experience proposed by Descartes' sceptical adversary, Michel de Montaigne. Forceful and provocative, The Matter of Mind will encourage lively debate on the norms and discourses of seventeenth-century philosophy."--Publishers description.